The unsteady Couette flow of a second grade fluid in a layer of porous medium - Hayat, T.; Khan, M.; Ayub, M.; Siddiqui, A.M. (Archives of Mechanics, 2005)
In this work, the two Couette flows of a second grade fluid are discussed in a porous layer when (i) bottom plate moves suddenly (ii) bottom plate oscillates. Laplace transform method is used to determine the analytic solutions. Expressions for the velocities, volume fluxes and frictional forces are constructed.